Dynamic deformations tests of Ni3Al based intermetallic alloy by using the split Hopkinson pressure bar technique - Jozwik, Pawel; Kopec, Mateusz; Polkowski, Wojciech; Bojar, Zbigniew (Journal of Mining and Metallurgy, Section B: Metallurgy, 2019)
In this work, the Ni3Al-based intermetallic alloy was subjected to room temperature dynamic plastic deformation tests by using a split Hopkinson pressure bar technique. The dynamic compression processes were carried out at strain rates in the range of (1.9×102 ÷ 1×104s-1). A strong impact of applied deformation conditions on microstructure and mechanical properties evolution in the examined Ni3Al intermetallic, was documented. Generally, very high maximum compressive stress values were obtained, reaching 5500 MPa for the sample deformed at the highest strain rate (i.e. 1×104s-1). The results of performed SEM/EBSD evaluation point towards an occurrence of dynamic recovery and recrystallization phenomena in Ni3Al samples deformed at high strain rates.